Association of rs142548867 (EEFSEC) and periodontitis Grade C in a young Brazilian population - Camila Schmidt STOLF; Tiago TAIETE; Paloma A. do NASCIMENTO; Hélvis E. S. PAZ; Enílson Antônio SALLUM; Karina Gonzalez Silvério RUIZ; Márcio Zaffalon CASATI; Renato Corrêa Viana CASARIN (University of São Paulo, 2023)
Abstract Periodontitis Stage III-IV, Grade C (PerioC) is a severe form of Periodontitis. The individual genetic background has been shown to be an important etiopathogenic factor for the development of this disease in young, systemically healthy, and non-smokers patients. Recently, after exome sequencing of families with a history of the disease, PerioC was associated with three single nucleotide variations (SNVs) - rs142548867 (EEFSEC), rs574301770 (ZNF136), and rs72821893 (KRT25) - which were classified as deleterious or possibly harmful by prediction algorithms. Objective Seeking to validate these findings in a cohort evaluation, this study aims to characterize the allele and genotypic frequency of the SNVs rs142548867, rs574301770, and rs72821893 in the Brazilian population with PerioC and who were periodontally healthy (PH). Methodology Thus, epithelial oral cells from 200 PerioC and 196 PH patients were harvested at three distinct centers at the Brazilian Southern region, their DNA were extracted, and the SNVs rs142548867, rs574301770, rs72821893 were genotyped using 5'-nuclease allelic discrimination assay. Differences in allele and genotype frequencies were analyzed using Fisher's Exact Test. Only the SNV rs142548867 (C > T) was associated with PerioC. Results The CT genotype was detected more frequently in patients with PerioC when compared with PH subjects (6% and 0.5% respectively), being significantly associated with PerioC (odds ratio 11.76, p=0.02). Conclusion rs142548867 represents a potential risk for the occurrence of this disease in the Brazilian population.